Concentrated vertical jetting mechanism for isotropically focused Zno/Si surface acoustic waves. (May 2019) - Jangi, M.; Luo, J.T.; Tao, R.; Reboud, J.; Wilson, R.; Cooper, J.M.; Gibson, D.; Fu, Y.Q.
Highlights: Experimental setting of vertical droplet jetting using circular surface acoustic wave (CSAW) devices with annular interdigitated transducers (AIDTs) fabricated on ZnO film coated silicon substrate. High-fidelity Computational Fluid Dynamics (CFD) using Direct Numerical Simulations (DNS) method is used to reproduce the experimental observations. Simulations involves two-phase flow modelling of droplet-air system, in which volume of fluid coupled with Level-set (VOF-LS) technique is used to capture the droplet deformation, jetting and atomisation processes. Based on the simulation results, the mechanism of droplet jetting by SAWs is explored. Abstract: This paper investigates vertical droplet jetting using circular surface acoustic wave (CSAW) devices with annular interdigitated transducers (AIDTs) fabricated on ZnO film coated silicon substrate. The surface vibration on the CSAW devices was simulated using finite element analysis and characterised using laser vibrometry. Results showed that focused wave patterns and compact nodal distributions of vibration were formed at the centre of ZnO/Si CSAW device, which is contrast to an anisotropic wave distribution patterns generated by the same pattern of AIDTs fabricated on 128° Y-cut LiNbO3 . Simulation of liquid jetting induced by the isotropically focused CSAW was performed using coupled Volume of Fluid and Level-Set method. Results showed that a sharp and cylindrical liquid column was generated from the ZnO/Si CSAW device induced by acoustic energy coming from all directions within the plane due to the in-plane isotropic nature of the ZnO thin films. The simulation enabled us to capture the different streaming/jetting processes induced by the anisotropic distributions of acoustic pressure generated by the AIDTs on the 128° Y-cut LiNbO3 CSAW device. The concentrated vertical droplet jetting behaviour from the ZnO/Si CSAW devices was investigated experimentally and supported the simulated results.